2018
DOI: 10.1002/hpm.2513
|View full text |Cite
|
Sign up to set email alerts
|

Surviving neoliberalism, maintaining values: Community health mergers in Victoria, Australia

Abstract: This study offers insights into decision-making processes geared towards protecting the comprehensiveness of PHC service delivery for disadvantaged communities, ensuring financial viability, and surviving neoliberal economic policy whilst preserving communitarian values. These are relevant to an international audience, within a global context of rising health inequities, increasingly tight fiscal environments, and growing neoliberal influences on health policymaking and funding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
2
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…Our findings particularly illuminate previous suggestions of poor information systems and monitoring of mental health in LMICs and affirms that provincial government managers hold significant power over programme funding and information . Views from this study district further highlighted the discrepancies between the purported support by state government for frontline health care provisioning and actual resourcing of such services . In our findings state and formal health system hierarchies emerged as forms of power that guided the referral and collaborative behaviour of the mental health service network.…”
Section: Discussionsupporting
confidence: 82%
“…Our findings particularly illuminate previous suggestions of poor information systems and monitoring of mental health in LMICs and affirms that provincial government managers hold significant power over programme funding and information . Views from this study district further highlighted the discrepancies between the purported support by state government for frontline health care provisioning and actual resourcing of such services . In our findings state and formal health system hierarchies emerged as forms of power that guided the referral and collaborative behaviour of the mental health service network.…”
Section: Discussionsupporting
confidence: 82%
“…This method was selected to focus the data analysis on exploring perceptions of legitimacy changes from the point of view of different stakeholder groups. To develop the analysis template, desired merger outcomes identified during the study's first phase of data collection in 2014 (Roussy and Livingstone, 2018) were classified according to the type of legitimacy they fit best with, using Suchman's typology (Suchman, 1995) (Table 2). The draft template was discussed among all authors, then trialled by the first author during a preliminary coding round with three transcripts.…”
Section: Methodsmentioning
confidence: 99%
“…In 2014, we began a longitudinal case study of two such organisations. Our first phase of data collection demonstrated that their primary driver for amalgamating was a desire to manipulate and enhance their long-term organisational legitimacy in the face Merger effect on health organisations of neoliberalisation in order to secure their survival and ongoing capacity to deliver comprehensive PHC services to disadvantaged populations (Roussy and Livingstone, 2018).…”
Section: Organisational Legitimacymentioning
confidence: 99%
See 1 more Smart Citation
“…DSW's and those who work within health and community services, are at high risk of a psychological response to workplace stress (Harries et al 2015). The burdens are immense with so many disability businesses merging or discontinuing services in Victoria (Roussy & Livingstone, 2018). "The NDIS has created an environment where the challenges for organisations are intensified, creating more ambiguity, conflict and demands for DSW" (Marianne Hubbard, 2019).…”
Section: Lack Of Employee Benefitsmentioning
confidence: 99%